THE EXPERIENCE OF STIGMA: THE DYNAMICS OF LIPSTICK BANS IN SCHOOLS - Dhuha Hadiyansyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study explores adolescent girls' experiences with the stigma and prohibition of lipstick use in schools through a qualitative lens. Using a case study method and in-depth interviews with 10 young women aged 18–22 in Jabodetabek, the research is grounded in Eagly's Social Role Theory and analyzed thematically. Findings reveal that the lipstick ban reflects efforts to maintain traditional gender roles, where academic focus is prioritized over personal expression through appearance. Teachers’ bans and parental directives show how gender norms are reinforced in both school and home environments. The stigma from peers and educators illustrates how social expectations about female appearance shape interactions and self-perception. However, the absence of stigma in some cases indicates varying levels of social acceptance and suggests shifting, more flexible norms. Respondents were divided: some supported the ban for preserving academic focus, while others saw it as a limitation on personal expression. These perspectives highlight the tension between conformity to traditional roles and the desire for self-expression. Overall, the study underscores how gender expectations shape students' experiences of cosmetic use and how evolving social values may influence the perception and acceptance of such school policies.